6(x + 3y) - (5z - x)
If x= 3, y= 2andz= 5 find the value
Answers
Answered by
38
Given x = 3 , y = 2 , z = 5
=> 6(x + 3y) - (5z - x)
Substituting the given values
=> 6(3+3(2)) - (5(5)-3)
=> 6(3+6) - (25-3)
=> 6(9) - 22
=> 54 - 22
=> 32
Answered by
6
6(3+3(2)-(5(5)-3)
6(3+6)-(25-3)
54-22
32
Answer is 32
I hope that answer is helpful
pls mark me as brainlist
Similar questions
Environmental Sciences,
3 months ago
Environmental Sciences,
3 months ago
English,
7 months ago
Psychology,
7 months ago
Music,
1 year ago
Math,
1 year ago